Mother's little helper? Contrasting accounts of benzodiazepine and methadone use among drug-dependent parents in the UK. (December 2014) - Chandler, Amy; Whittaker, Anne; Williams, Nigel; McGorm, Kelly; Cunningham-Burley, Sarah; Mathews, Gillian
Abstract Aims: To explore the ways in which opioid-dependent parents accounted for their use of opioids and benzodiazepines during and after pregnancy. Methods: Longitudinal qualitative interviews [n = 45] with 19 opioid-dependent adults recruited in Scotland, UK, were held during the antenatal and post-natal period. Interviews focused on parenting and parenting support within the context of problem drug use and were analysed using a narrative informed, thematic analysis. Findings: The majority of participants described using benzodiazepines in addition to opioids. Almost all indicated a desire to stop or reduce opioid use, whereas cessation or reduction of benzodiazepines was rarely prioritised. In stark contrast to opioid dependence, benzodiazepine dependence was portrayed as unproblematic, therapeutic and acceptable in the context of family life. Whereas opioid dependence was framed as stigmatising, benzodiazepine use and dependence was normalised. An exception was benzodiazepine use by men which was occasionally associated with aggression and domestic abuse. Conclusions: Drug-dependent parents attach different meanings to opioid and benzodiazepine use and dependence in the context of parenthood. Divergent meanings, and stigma, may impact on stated commitment to stability or recovery from dependent drug-use. Attention should be paid to the way in which policy and practice regarding OST and benzodiazepines reflects this divergence.